Factors influencing the satisfaction level of college students in China: Literature analysis based on grounded theory - Gu, Qiongying; Lu, Guodong (Frontiers in Psychology, 2023)
The factors influencing college students’ satisfaction level are the basis and premise of satisfaction research. Based on a qualitative analysis of 48 literatures on college students’ satisfaction using NVivo12 software, we found that the influencing factors of college students’ satisfaction in China are composed of seven dimensions: school reputation, school environment, personal improvement, organisation and management, logistics support, teaching quality, and charges and subsidies. Among them, teaching quality, school environment, organisation and management, and logistics support are the core categories. Further, school reputation, school environment, organisation and management, logistics support, teaching quality, and charges and subsidies are external factors, while personal improvement is an internal factor. To improve the satisfaction level of college students, the two dimensions of external and internal factors must be taken into account, with external factors being given more attention.